Perancangan Desain Interior Rumah Tinggal Tema Classic Dalam Pelaksanaan Magang Pada CV. Equipment Indonesia Perkasa - Aulia, Rachel; Fernanda Dwi Cahyani; Putri Sekar Hapsari; Tri Prasetyo Utomo (Sanggitarupa, 2024)
The Independent Campus Internship Program is an initiative from the Ministry of Education and Culture which aims to bridge the gap between theory learned on campus and practice in the world of work. The Independent Campus Learning Program (MBKM) FSRD internship/work practice scheme held by the Indonesian Institute of the Arts Surakarta, is implemented with the aim of providing opportunities for students to be able to apply the knowledge they have learned during the lecture process in the real world of work. The internship program is implemented for 4 (four) months, 15 (fifteen) weeks, starting from March 13 2024 to June 28 2024. The student internship activity schedule starts at 09.00 - 16.00 WIB, from Monday to Friday. Through the guidance of mentors from CV. Equipment Indonesia Perkasa, students gain new skills and industry insight relevant to their field of study. The results of this program are expected to show increased student competency and work readiness, as well as gaining a lot of new knowledge during the process of working on the project. Keywords: Classic. Design, Internship, MBKM, Residance.